How were lipofilling cannulae designed and are they as safe as we believe? - Memet Yazar; Sevgi Kurt Yazar; Kamuran Zeynep Sevim; Fatih Irmak; Merva Soluk Tekesin; Erol Kozanoğlu; Semra Karsidag (Indian Journal of Plastic Surgery)
Background: Most practitioners in plastic surgery believe that blunt tipped cannulae are safer. Interestingly, there is no study about their safety, and the problem is exactly this. As the use of blunt tipped cannulae is somehow difficult, some surgeons try other extreme alternatives, such as sharp and cutting tipped injection needles. But, they can cause complications such as vessel damage. According to these hypotheses, we tried to design a cannula which would ease the application of lipofilling and which would minimise the trauma. Contrary to the injection needle, the tips of the cannula would be blunter, and trauma would be diminished. Objectives: After designing such a cannula, we compared it with the most frequently used Coleman type cannulae with regard to ease in utilisation, and safety. We also tried to evaluate the potential for trauma, of the regularly used cannulae. Materials and Methods: In the first part, the penetration capacity of all cannulae was measured and compared, and in the second part, the tissue damage was evaluated in an experimental model. Results: According to the statistical and histological findings, the pointed-tip cannulae, blunted to a certain degree, can be applied easily through the tissues. The surgeon works more comfortably and we have noted that these cannulae cause less tissue damage.